2017
DOI: 10.1007/s00540-017-2363-x
|View full text |Cite
|
Sign up to set email alerts
|

An update on the management of postoperative nausea and vomiting

Abstract: Postoperative nausea and vomiting (PONV) and postdischarge nausea and vomiting (PDNV) remain common and distressing complications following surgery. PONV and PDNV can delay discharge and recovery and increase medical costs. The high incidence of PONV has persisted in part because of the tremendous growth in ambulatory surgery and the increased emphasis on earlier mobilization and discharge after both minor and major operations. Pharmacological management of PONV should be tailored to the patients' risk level u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
94
4
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(103 citation statements)
references
References 82 publications
1
94
4
4
Order By: Relevance
“…PONV is a very common complication following opioid-based intravenous PCA 26 . PONV can cause dehydration, electrolyte imbalance, postoperative bleeding, wound dehiscence, and pulmonary aspiration, and further aggravate patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…PONV is a very common complication following opioid-based intravenous PCA 26 . PONV can cause dehydration, electrolyte imbalance, postoperative bleeding, wound dehiscence, and pulmonary aspiration, and further aggravate patient discomfort.…”
Section: Discussionmentioning
confidence: 99%
“…Early postoperative rehabilitation is affected by PONV(6),and the incidence of PONV varies from 20-80% (7,8) and is affected by surgical time, sex, and postoperative opioid (9). As the proportion of woman is quite high in rheumatoid patients, they are expected to be at high risk for PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Contemporary literature points to the fact that female sex possesses a strong predictive factor for the occurrence of PONV [14], and a high incidence of PON and POV is expected. In addition to sex, the type of surgical intervention in terms of gynecological laparoscopic surgery also influences the highly expected incidence of PONV, up to 80% [3]. For ethical reasons, this study did not include a control group that would receive a placebo, and the total incidence of PON and POV remains only at prediction level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients regard vomiting as the most undesirable complication of anesthesia and qualify it as a more unpleasant sensation than pain [1,2]. The incidence of PONV in adult population is 30% [3], and in high-risk population such as gynecologic and laparoscopic surgery, it can be up to 80% [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation